Choline preparations in the treatment of asthenic states: modernity and perspectives (A Clinical Case Presentation) - Yu. V. Bykov; R. A. Bekker (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In this article, we want to present the reader with an interesting clinical case from authors’ practice, which, in our opinion, clearly demonstrates the efficacy and safety of using Gliatilin (choline alfoscerate) as a part of combination therapy in a 19-year-old man with so-called «long COVID syndrome», manifesting itself predominantly as mix of symptoms of asthenia, depression, anxiety, sleep and cognitive difficulties. This patient, for his ideological reasons and beliefs, refused taking antidepressants, anxiolytics, as well as any other psychotropic drugs. At the same time, the patient asked for help in choosing «a treatment, which will consist of only natural ingredients».